Metode Sains: Membaca Pemikiran Epistemologis al Attas dan Wall - Usmanul Khakim; Khasib Amrullah; Hifni Nasif (Civiliza Publishing, 2021)
This paper will discuss “the scientific method” which proposed by al Attas and Thomas F Wall. The main question will be discussed here is “where is the position of religious knowledge in the scientific method?”; where religious knowledge as a source of truth. In other words, “is the religious knowledge can be accommodated into the scientific method?” Based on this main quetion, the study aimed to compare the thoughts of al Attas and Wall in the this theme. The two figures were chosen; they are both contemporary thinkers are the philosophers of science, where al Attas represents Islamic science philosopher and Wall represents Western science philosopher. This article is a literature study; while content and comparative analysis will be implemented as the methods of this study. Besides, the philosophical aproach will be take a role in this discussion. The result of this study is Wall didn’t accommodate religious knowledge into the scientific method. Wall concluded that the truth is based on the researcher subjective; which is formulated into a hyphothesis. On the other hand, al-Attas accepted religious knowledge (read: Islam) as objective truth into scientific method.